2008
DOI: 10.1073/pnas.0801853105
|View full text |Cite
|
Sign up to set email alerts
|

Decreased corticolimbic allopregnanolone expression during social isolation enhances contextual fear: A model relevant for posttraumatic stress disorder

Abstract: Mice subjected to social isolation (3-4 weeks) exhibit enhanced contextual fear responses and impaired fear extinction. These responses are time-related to a decrease of 5␣-reductase type I (5␣-RI) mRNA expression and allopregnanolone (Allo) levels in selected neurons of the medial prefrontal cortex, hippocampus, and basolateral amygdala. Of note, the cued fear response was not different between group housed and socially isolated mice. In socially isolated mice, S-norfluoxetine, a selective brain steroidogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(290 citation statements)
references
References 44 publications
11
277
0
2
Order By: Relevance
“…Rather, dysfunction in clinically relevant brain circuitry seems to be already manifested shortly after massive traumatic events. Consistent with this idea, studies based on animal models have revealed that cortical GABA neurons can be modulated by allopregnanolone soon (3-4 weeks) after subjecting animals to experimental fearful stimuli (30). The increased GABA tone could increase regionally synchronized neuronal activity (31) and activity in ␥-band power (32), which has been found to be correlated with ALFF (15).…”
Section: Discussionmentioning
confidence: 61%
“…Rather, dysfunction in clinically relevant brain circuitry seems to be already manifested shortly after massive traumatic events. Consistent with this idea, studies based on animal models have revealed that cortical GABA neurons can be modulated by allopregnanolone soon (3-4 weeks) after subjecting animals to experimental fearful stimuli (30). The increased GABA tone could increase regionally synchronized neuronal activity (31) and activity in ␥-band power (32), which has been found to be correlated with ALFF (15).…”
Section: Discussionmentioning
confidence: 61%
“…Social instability: Just like the random cage cohort HI model, PTSD-like symptoms can be created using social isolation (SI). Isolation for at least 1 d in adult mice leads to more contextual freezing and impaired fear extinction during FS-like fear conditioning [69] . Overlap with the prior HI model was found in the form of increased anxiety and HPA changes, although the latter is formed by impaired suppression and higher baseline levels of corticosterone in the SI model [70] .…”
Section: Housing Instabilitymentioning
confidence: 99%
“…Because deuterated 3α-androstanediol is not available, deuterated 3β-androstanediol was used as the internal standard for 3α-androstanediol. Each steroid of interest was then derivatized for GC-MS (Pibiri et al, 2008;Pinna et al, 2000). Mass spectrometric analysis was conducted in the standard electron impact mode for all neuroactive steroid measurements.…”
Section: Hormone Analysismentioning
confidence: 99%